2009
DOI: 10.1590/s0066-782x2009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Troponina cardíaca T para estratificação de risco na insuficiência cardíaca crônica descompensada

Abstract: The increase in cTnT is associated with a bad prognosis in decompensated HF and the degree of this increase can help the risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…From this perspective, measurement of the troponin level brings additional prognostic information in patients with acute HF, as several studies confirmed [ 72 , 74 , 75 ]. Cardiac troponin was associated with readmission rates and mortality risk in patients with acute HF [ 69 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, measurement of the troponin level brings additional prognostic information in patients with acute HF, as several studies confirmed [ 72 , 74 , 75 ]. Cardiac troponin was associated with readmission rates and mortality risk in patients with acute HF [ 69 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Del Carlo et al described the relevance of cardiac troponin T for risk stratification 12. Santos analyzed the quality of life in this group of patients 13.…”
Section: Methodsmentioning
confidence: 99%
“…Other small scale studies [38,39] have demonstrated that elevated troponin I is associated with lower ejection fraction, higher systolic pulmonary artery pressure and increased length of hospital stay. Moreover, abnormal troponin T is a predictor of increased risk of HF readmission and mortality [40,41]. These associations have persisted up to 3 years from the index hospitalization.…”
Section: Heart Failurementioning
confidence: 98%
“…Del Carlo C.H. et al [40] 70 patients with chronic HF worsening that needed hospitalization were studied.…”
Section: Heart Failurementioning
confidence: 99%